Improving Maritime English Speaking Skills through TikTok Media among Nautical Studies Cadets of Sorong Merchant Marine Polytechnic - Yulianingsih, Lilik; Nofriska Sudrimo, Sella; Manuputty, Piter; Lia Masan, Agustinus (Jurnal Indonesia Sosial Sains, 2025)
Speaking skills are one of the important skills in English that has a crucial role in oral communication, especially in maritime education which requires cadets to master technical and communicative competencies. The results of initial observations at the Sorong Shipping Polytechnic show that cadets of the Nautical 2C Study Program still face obstacles in the form of limited vocabulary, low confidence, and difficulties in grammar and pronunciation, which have an impact on low speaking skills. This class action research aims to improve cadets' Maritime English speaking skills through the integration of TikTok media as a means of digital learning. The research was carried out collaboratively in three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation sheets, speaking tests, pre-tests and post-tests, and interviews. The results showed a consistent improvement in both learning activities and speaking skills. The active participation of cadets increased from cycle I (55.29% of the fair category) to cycle III (75% of the good category). The average value of speaking skills increased from 65 (cycle I) to 77.12 (cycle III), with learning completeness increasing from 11.76% in cycle I, to 88.23% in cycle III. The post-test results strengthened this finding with an average score of 83.76 and 88.23% of cadets achieving the KKM. Interviews show that more than 85% of cadets consider TikTok effective in increasing motivation, creativity, and confidence in practicing speaking. It can be concluded that the integration of TikTok in Maritime English learning has proven to be effective in improving speaking skills, especially in terms of comprehension, fluency, and pronunciation, as well as encouraging motivation and active involvement of cadets.